SYNTHESIS, CRYSTAL STRUCTURE AND PHOTOLUMINESCENCE PROPERTIES OF A NEW RARE-EARTH CARBONATE Na3Eu(CO3)3·6H2O - Zhang, Rong-Hua; Zhao, Dan; Huang, Min; Yang, Rui-Juan; Ma, Fa-Xue; Fan, Yun-Chang (Journal of the Chilean Chemical Society, 2017)
A new sodium europium carbonate hydrate, Na3Eu(CO3)3·6H2O, has been prepared using the hydrothermal method, and its structure was determined by single crystal X-Ray diffraction analysis for the first time. It crystallizes in the polar hexagonal space group P63 with a = 11.382(9) Å, c = 5.989(5) Å, V = 672.06(9) Å3, Z = 2, Mr = 509.06, Dc = 2.516 g/cm3, F(000) = 492, μ(MoKα) = 4.84 mm-1, R1 = 0.015 and wR = 0.038. The structure features a three-dimensional（3D） framework composed of planar (CO3)2- triangles, Eu3+ ions and Na+ ions, which delimits 1D infinite chains with a hexangular star appearance along the c-axis. The IR spectrum and the self-activated photoluminescence properties were studied. Under the excitation of near UV light (395nm), it shows strong red emission at 618 nm with a lifetime of 348.7 μs. Present research indicates that Na3Eu(CO3)3·6H2O is a promising red phosphor for white light-emitting diodes.